2015
DOI: 10.1097/nen.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

Sur1-Trpm4 Cation Channel Expression in Human Cerebral Infarcts

Abstract: In animal models of stroke, spinal cord injury, and subarachnoid hemorrhage, transient receptor potential melastatin 4 (Trpm4), a non-selective monovalent cation channel, is transcriptionally upregulated in neural and vascular cells. In these contexts, Trpm4 has been shown to co-associate with sulfonylurea receptor 1 (Sur1) to form Sur1-Trpm4 channels, which play a critical role in cytotoxic edema, accidental necrotic (oncotic) cell death, blood-brain barrier (BBB) breakdown and formation of vasogenic edema. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 34 publications
(55 reference statements)
1
68
1
2
Order By: Relevance
“…Together, the above experiments indicated that AQP4 M1 and M23 co‐associate with the SUR1‐TRPM4 heteromer through physical co‐associations with both TRPM4 and SUR1. Since direct interaction of SUR1 with TRPM4 has been validated in previous reports (Chen et al, ; Woo et al, ; Mehta et al, ), these experiments were not repeated here.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Together, the above experiments indicated that AQP4 M1 and M23 co‐associate with the SUR1‐TRPM4 heteromer through physical co‐associations with both TRPM4 and SUR1. Since direct interaction of SUR1 with TRPM4 has been validated in previous reports (Chen et al, ; Woo et al, ; Mehta et al, ), these experiments were not repeated here.…”
Section: Resultsmentioning
confidence: 98%
“…Normally, astrocytes constitutively express high levels of AQP4 (Nielsen et al, ), but do not express SUR1 or TRPM4 (Chen and Simard, ; Chen et al, ; Mehta et al, ; Simard et al, ). Thus, immunohistochemistry was used to determine if TRPM4 and SUR1 were upregulated in cerebellar astrocytes following cold injury.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27 The hypothesis is further evidenced by the coexpression of Sur1 and Trpm4 in necrotic endothelial cells and neurons in postmortem brain specimens from patients with focal cerebral ischemia, and the upregulated Sur1-Trpm4 channels were associated with blood-brain barrier disruption and cerebral edema. 28 Retrospective studies in diabetics with acute ischemic stroke and used sulfonylurea around the onset have suggested a protective role of sulfonylurea in blood-brain barrier. 12,13 However, the types and dosages of sulfonylurea agents varied in these two studies, leading to inconclusive findings.…”
Section: Discussionmentioning
confidence: 99%